Correlational analysis y geochemistry characterization of the mineralization from the basin of the rivers Chilca - Mala - Omas. Department of Lima. Peru - Rivera, Hugo (2009)
The current geochemnical-statistical study involves thirty-seven chemistry elements involving fourteen of these called heavy metals such As, Cd, Cr, Cu, Fe, Hg, Mo, Ni, Pb, Sb, Sn, V, W, Zn collected in active stream sediments from Chilca, Mala and Omas rivers located in the department of Lima, Peru. The filonean mineralization ocurrences of Cu, Pb, Zn, the abundance of trace elements and the correlation multivariable of the elements in the three rivers reflects the prevailing economic mineralization, in the Chilca river Zn, Cd, Pb in Mala river Cu, Co, Cr and in the Omas river Cu, Pb, Zn. The other elements are not pathfinder of this mineralizations because of the absence of good correlation between them, suggesting different source, at the morfology of the deposit and the erosion level of the surface. It has been determined that Chilca River has exceeded permissible levels in As and target level in Cd-Cd-Zn. The Mala River exceeded permissible level in As and the target level in Cu-Cd-Cr. Omas River exceeded in Cu and target level in As-Cd-Cr-Zn.